One hundred and eighteen years of the German health insurance system: are there any lessons for middle- and low-income countries? - Bärnighausen, Till; Sauerborn, Rainer (Social science & medicine, 2002)
A number of low and middle income countries (LMICs) are considering social health insurance (SHI) for adoption into their social and economic environment or striving to sustain and improve already existing SHI schemes. SHI was first introduced in Germany in 1883. An analysis of the German system from its inception up to today may yield lessons relevant to other countries. Such an analysis, however, is largely lacking, especially with regard to LMICs. This paper attempts to fill this gap. For each of the following lessons, it considers if and under which conditions they may be of relevance to LMICs. First, small, informal, voluntary health insurance schemes may serve as learning models for fund administration and solidarity, but in order to achieve universal coverage government action is needed to formalise these schemes and to introduce a principle of compulsion. Once compulsory health insurance exists for some people, incremental expansion of coverage to other regions and social groups may be feasible to achieve universality. Second, in order to ensure sustainability of SHI, the mandated benefit package should be adapted incrementally in accordance with changing needs, values and economic circumstances. Third, in a pluralistic SHI system equity, as well as risk pooling and spreading, can be enhanced if funds merge. The optimal number of funds, however, will depend on the stage of development of the SHI system as well as on other objectives of the system, including choice and competition. A risk equalisation scheme may prevent the adverse effects of risk selection, if competition between insurance funds is introduced into the system. Fourth, as an alternative to both state and market regulation, self-governance may serve as a source of stability and sustainability as well as a means of decentralising and democratising a health care system. Finally, costs can be successfully contained in a fee-for-service system, if cost-escalating provider behaviour is constrained by either political pressure or technical means.